Fatty acid digestibility in gilthead sea bream fed diets containing native, re‐esterified or acid vegetable oils. (5th April 2016) - Trullàs, C.; Fontanillas, R.; Tres, A.; Sala, R.
Abstract: Re‐esterified vegetable oils are obtained from a chemical esterification reaction between vegetable acid oils and glycerol. Due to their properties, it is expected that they have a higher nutritive value than their corresponding acid oils and a better digestibility than their native counterparts. The aim of this study was to determine the effect of re‐esterified oils with a different monoacylglycerol (MAG) and diacylglycerol (DAG) content, produced from palm or rapeseed, on fatty acid digestibility in gilthead sea bream ( Sparus aurata ). Triplicate groups of fish were fed nine experimental diets containing different oils during 28 days. For each source, four different types of oil were used: native, re‐esterified low or high in MAG and DAG and acid. A commercial fish oil was used for the control diet. Diets containing re‐esterified oils had better apparent digestibility coefficients (ADC) of total fatty acids than acid oil diets. Re‐esterified oils do not negatively affect apparent digestibility coefficients of fatty acids when compared to their corresponding native oils and could be incorporated as a source of energy in diets for gilthead sea bream. An improvement in digestibility compared to the native oil diet was only obtained in palm re‐esterified oil high in MAG and DAG.